History, Fiction and Metafiction in the Novels About the Sarajevo Assassination Written by Georges Perec and Zlatko Topcic - Melida Travančić (Društvene i Humanističke Studije, 2019)
When a historical event is transposed into literary discourse, the most important questions are: How do writers shape the narrative? What do they point out? And, what do they insist on when developing the story? The focus of the novel written by Georges Perec, The Sarajevo Assassination, as well as the one written by Zlatko Topcic, June 28, 1914, is not history; they use history only as the basis and subject matter. The basis of these novels is, actually, the attitude to history, that is, the deconstruction of the “great story” of the assassination. Perec and Topcic embark on their own “exploration” of history and treat the official historical narrative critically and creatively. At the forefront is the connection between the historical and the literary discourse, the connection between faction, fiction and metafiction. In both novels historical documents are turned into literary documents. The text is shaped using postmodern writing techniques. In some parts, emphasized self-reference suspends the referential illusion. In general, exploring the issue of the connection between fiction and faction, the novels largely question (and shift) narrative strategies and structures.